Partial HELLP Syndrome Complicated by Leukocytosis in Pregnant Woman Undergoing Intensive Care in a Hospital : Case Report - Richa Difayana Sari; Hana Iftitah Hidayati; Yuliana Arisanti (International Journal of Health Engineering and Technology, 2026)
HELLP syndrome (Hemolysis, Elevated Liver enzymes, and Low Platelet count) is a severe obstetric condition that may occur during pregnancy or postpartum, often associated with preeclampsia. Partial or incomplete HELLP syndrome presents a diagnostic challenge when only one or two of the three defining criteria are met. This report describes a 30-year-old woman, gravida 2 para 1 at 33–34 weeks of gestation, who developed eclampsia and partial HELLP syndrome complicated by severe leukocytosis. Despite an emergency cesarean section and intensive care management, including magnesium sulfate, corticosteroids, broad-spectrum antibiotics, and ventilatory support, the patient’s condition deteriorated to sepsis, acute respiratory distress syndrome (ARDS), and multi-organ dysfunction. Extreme leukocytosis (>40,000/µL) complicated the diagnostic process, mimicking infectious etiology. This case emphasizes the importance of differentiating inflammatory from infectious leukocytosis in HELLP syndrome and underscores the necessity of a multidisciplinary approach, timely delivery, and intensive monitoring. Even in its partial form, HELLP syndrome remains a life-threatening disorder that requires early recognition and aggressive management to improve maternal outcomes.